(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This paper presents a comprehensive analysis of the economic outcomes of Kyrgyzstan’s ten-year membership in the Eurasian Economic Union (EAEU). It explores GDP dynamics, trade expansion, labor migration, and investment influx. The findings highlight notable achievements alongside structural challenges. The paper concludes with recommendations for systemic reforms and technological modernization.